1999
DOI: 10.1038/sj.bjc.6690751
|View full text |Cite
|
Sign up to set email alerts
|

Serum p53 autoantibodies in patients with minimal lesions of ductal carcinoma in situ of the breast

Abstract: Five of 43 patients (11.6%) with ductal carcinoma in situ of the breast presented with p53 autoantibodies at diagnosis. Three seropositive patients demonstrated tumour sizes of ≤ 5 mm. There was no association of p53 autoantibody status with age, clinical presentation, histological subtype, tumour size, grading, p53 immunohistochemistry or hormone receptor status. © 1999 Cancer Research Campaign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Association with grade Increased lung vs bone metastases [22] 8% (8/101) ELISA Association with tumor grade Association with lack of ER [78] 26% (48/182) ELISA Association with histological grade [79] 12% (42/353) ELISA Association with shortened survival [80] 15% (9/61) ELISA Association with tumor size [81] 48% (39/82) ELISA No clinical correlation [82] 9% (15/165) ELISA + WB Association with shortened survival [83] 12% (5/43) ELISA No clinical correlation [84] 15% (115/1006) ELISA No clinical correlation [85] 19% (30/158) ELISA Association with stage Association with lack of ER Association with Ki-67 [86] ELISA: Enzyme-linked immunosorbent assay; ER: Estrogen receptor; IP: Immunoprecipitation; WB: Western blotting.…”
Section: % (14/155) Ip Using Cell Lysatesmentioning
confidence: 99%
“…Association with grade Increased lung vs bone metastases [22] 8% (8/101) ELISA Association with tumor grade Association with lack of ER [78] 26% (48/182) ELISA Association with histological grade [79] 12% (42/353) ELISA Association with shortened survival [80] 15% (9/61) ELISA Association with tumor size [81] 48% (39/82) ELISA No clinical correlation [82] 9% (15/165) ELISA + WB Association with shortened survival [83] 12% (5/43) ELISA No clinical correlation [84] 15% (115/1006) ELISA No clinical correlation [85] 19% (30/158) ELISA Association with stage Association with lack of ER Association with Ki-67 [86] ELISA: Enzyme-linked immunosorbent assay; ER: Estrogen receptor; IP: Immunoprecipitation; WB: Western blotting.…”
Section: % (14/155) Ip Using Cell Lysatesmentioning
confidence: 99%
“…Autoantibodies have been detected as early as DCIS 45 , but, again, the association of p53-specific antibodies and tumor stage has shown mixed results. A higher frequency of autoantibodies was observed in late stage breast cancer 43,46 .…”
Section: Autoantibody Detection In Breast Cancer: Clinical Parametersmentioning
confidence: 99%
“…Three of the 5 seropositive patients had lesions no larger than 5 mm. 38 The detection of autoantibodies may be used as an adjunct to more standard serologic tests being evaluated to aid in cancer diagnosis. Muller et al showed that the addition of p53 specific antibody detection to conventional tumor markers (CEA for colon cancer, AFP for hepatocellular carcinoma, CEA and CA15-3 for breast cancer, CA72-4 for gastric cancer) led to an increase in diagnostic sensitivity of 8% without decreasing specificity.…”
Section: Methods To Identify Serum Autoantibodies As Potential Diagnomentioning
confidence: 99%